PENGARUH FAKTOR-FAKTOR PRODUKSI TERHADAP TINGKAT PROFITABILITAS PENGRAJIN BATU BATA DI TALANG JAMBE KOTA PALEMBANG - Nur Alam, Hendri (Jurnal Ilmu Manajemen, 2013)
This study was conducted to determine the effect of Labor, Clay and machine against a brick craftsman level of profitability in the Gutters Jambe Palembang. This study uses interview techniques. The variables in this study are labor, raw materials and profitability. The analysis used. The analysis used in this study is multiple regression analysis. The result explained that the correlation coefficient (R) was 0.923. The independent variables can describe escara integrative variable bound by contributing 92.3%. Besidesthe F value was significant. It can be concluded tenag labor, raw materials and machinery has an influence on the profitability of Bricks Craftsmen.